2020
DOI: 10.1016/j.clinph.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Novel TMS-EEG indexes to investigate interhemispheric dynamics in humans

Abstract: Objective: To validate two indexes of interhemispheric signal propagation (ISP) and balance (IHB) by combining transcranial magnetic stimulation (TMS) and electroencephalography (EEG). Methods: We used TMS-EEG to non-invasively stimulate the two hemispheres of 50 healthy volunteers and measured interhemispheric dynamics in terms of ISP and IHB. We repeated our evaluation after three weeks to assess the reliability of our indexes. We also tested whether our TMS-EEG measures were correlated with traditional inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 46 publications
8
42
0
Order By: Relevance
“…Surprisingly, the stimulation of the UH revealed, on the contrary, a preservation of the interhemispheric suppression mechanism, similarly to what we observed in the healthy brain. Then, we computed an index, that is, IHB, reflecting the balance between the two hemispheres, which we recently validated in a large sample of 50 old and young healthy volunteers (Casula et al, 2020). We found an abnormally higher IHB in stroke patients, compared to healthy volunteers, revealing an imbalance between the two hemispheres.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, the stimulation of the UH revealed, on the contrary, a preservation of the interhemispheric suppression mechanism, similarly to what we observed in the healthy brain. Then, we computed an index, that is, IHB, reflecting the balance between the two hemispheres, which we recently validated in a large sample of 50 old and young healthy volunteers (Casula et al, 2020). We found an abnormally higher IHB in stroke patients, compared to healthy volunteers, revealing an imbalance between the two hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…ISP has already been used by previous works (Jarczok et al, 2016; Määttä et al, 2017; Voineskos et al, 2010) even if these studies did not verify the sensitivity nor the reliability of this measure. We recently tested ISP in a large sample of healthy volunteers, founding an extremely low intersubject variability among the 50 participants tested (Casula et al, 2020). Although the physiological mechanism underlying ISP has not been fully elucidated, it is likely mediated by transcallosal inhibitory fibers, given its strict correlation with microstructural integrity of callosal fibers (Voineskos et al, 2010), a result that we confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The small number of molecules that proceed through the pipeline into human research can encounter further failure due to lack of efficacy in clinical trials. These challenges to Transcranial magnetic stimulation (TMS) is a non-invasive brain stimulation technique which, in combination with electroencephalography (EEG), enables a fast and accurate assessment of human brain excitability in health 2,3 and pathological conditions 4 . TMS-EEG output measures can be interrogated in the time 5 and time-frequency domains 6 , providing different information about cortical processes 7 .…”
Section: Introductionmentioning
confidence: 99%